ACTIVITIES OF YOUTH ORGANIZATIONS IN THE FIELD OF EMPLOYMENT ON THE TERRITORY OF THE ZARAFSHAN OASIS DURING THE YEARS OF INDEPENDENCE OF UZBEKISTAN (2017-2022) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The main purpose of the study is the historical process of the activity of youth organizations in the field of youth employment on the territory of the Zarafshan oasis. A source-based, structural-functional, comparative-historical method was used. The study of the problem was carried out according to the chronological sequence, comparative analysis and regional approach. In particular, the Samarkand Bukhara and Navoi regions are compared, where youth organizations such as the Youth Union of Uzbekistan, the Agency for Youth Affairs, work on the basis of action plans related to the employment of young people. Based on the results obtained, the article examines the historical role and regulatory framework of youth organizations. The social significance of the events held by youth organizations on the example of the Zarafshan oasis. The essence of the laws aimed at the comprehensive development of the young generation of Uzbekistan in the field of employment.
Keywords: youth, youth organizations, legislation, employment, employment, advantage, improvement.